Optimization of Early Detection by Sat Intelkam to Prevent Motor Vehicle Theft Under the Jurisdiction of Jepara Police (Indonesian Journal of Police Studies, 2024)
The research was motivated by the high number of motor vehicle theft cases in the Jepara Police jurisdiction which ranks third in the order of the highest criminal acts. Early detection efforts have been made by Jepara Police, but it still often occurs. Therefore, a study was conducted that aimed to provide an analysis of the management of the implementation of early detection activities by the Intelligence and Security Unit of Jepara Police and the competence of Intelligence Unit members in the implementation of early detection. This research was conducted using a qualitative approach and with field research. Data collection was carried out by means of interviews, observations, and document studies. The theories used are management theory, SWOT theory and competency theory. While the concepts used are the concept of early detection based on Perkabik No. 1 of 2013, and the concept of Intelkam based on Perkap no. 2 of 2021 concerning the Organizational Structure and Work Procedures at the Resort Police Level and Sector Police. The research found that in the management of the implementation of early detection and competence of members of the Intelligence and Security Unit, it is still not as expected. It was found that there are obstacles such as the absence of the latest planning administration products, there are still head of the unit who have not been able to delegate their duties to their members, there is a lack of members so that the quality of information retrieval is lacking, and also a lack of direct supervision of members. The competence of members of the Jepara Police Intelligence and Security Unit is also still lacking with the discovery of information that there are still members who have not been trained, still have not mastered the Cover Technique properly, and there is still a reluctance to excel from each member. From the results of the study, it can be concluded that there is still a need for optimization of early detection by the Jepara Police Intelkam Unit.
Keywords: Optimalisasi, deteksi dini, mencegah, curanmor, Satuan Intelkam